FRET-based probe for monitoring pH changes in lipid-dense region of Hct116 cells - Reddy, Upendar G.; Anila, H. A.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Organic Letters, 2015)
A rhodamine conjugate (L) with a pseudo Stokes shift of 165 nm is used for probing changes in solution pH under physiological conditions. This reagent is found to be nontoxic, and the luminescence response could be used for imaging changes in endogenous pH induced by dexamethanose (DMT) in the endoplasmic reticulum.